The experiences of registered nurses in polytechnic baccalaureat degree programmes : an interpretive phenomenological study: a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Nursing at Massey University - Seaton, Philippa (Massey University, 1998)
This interpretive phenomenological study examines the experience of registered nurses who returned to study for a baccalaureate degree in nursing at polytechnics in New Zealand. Although there are substantial numbers of registered nurses undertaking a first degree in nursing in the polytechnics, little New Zealand research exists related to this particular student group The purpose of this research was to describe some of the common meanings embedded in the registered nurse students' experiences, in order to reveal new possibilities for teaching and learning in registered nurse education. Eleven registered nurses who had graduated from baccalaureate nursing degree programmes provided data, ten through interviews, and one through a written narrative. The transcribed interview texts and the written narrative were analysed using interpretive methodology based in a background philosophy of Heideggerian phenomenology. Two major themes, Experiencing thinking, and Experiencing community, emerged. Closely interwoven, these themes describe how the registered nurses understood their degree experience as impacting on their thinking, and how sharing learning with other registered nurses contributed to changes in thinking. For registered nurses, clinical practice always constitutes the background to their degree studies. For some registered nurses, learning to think questioningly, opens up new possibilities, in nursing practice and is a significant feature of the degree experience. For others, the degree is a reawakening of their expertise and understanding of their practice world as it is shared with others. The study describes how the common teaching and learning practices of reading, writing, and dialogue can contribute to students' thinking and understanding are described. The central importance of learning with other registered nurses as part of the degree experience is explored. Contrary to the conventional notion of learning as an individual endeavour, these registered nurses describe how learning is a shared experience. The findings of this study are discussed in terms of the possibilities for teaching and learning in nursing education. Gabrielle Hall, my colleague. I am very grateful for your support. Thank you for the times you have been so willing to help with my teaching and professional responsibilities to give me time to write. You have been a wonderful listener, and companion in conversations about registered nurse education. My friend Carol Murphy, for proof-reading, and your continuing support. All the registered nurse students who wittingly, or unwittingly, have contributed to this research through the conversations we have had over the years, and my colleagues who likewise, have shared their experiences with registered nurse students, thank you. Although they must remain anonymous. I extend my thanks to those polytechnics, particularly the nursing departments, who accepted my proposal and consented to assist me in gaining participants Finally, I would like to acknowledge and thank the Otago Polytechnic Research and Development Committee for their support, and the grant towards the cost of this study. My thanks also go to the Nursing and Midwifery department who have supported me with professional development time for writing this thesis.
Keywords: New Zealand; Nursing -- Study and teaching; Nursing students